2021
DOI: 10.1007/s40766-021-00020-z
|View full text |Cite
|
Sign up to set email alerts
|

Applications of large deviation theory in geophysical fluid dynamics and climate science

Abstract: The climate is a complex, chaotic system with many degrees of freedom. Attaining a deeper level of understanding of climate dynamics is an urgent scientific challenge, given the evolving climate crisis. In statistical physics, many-particle systems are studied using Large Deviation Theory (LDT). A great potential exists for applying LDT to problems in geophysical fluid dynamics and climate science. In particular, LDT allows for understanding the properties of persistent deviations of climatic fields from long-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 287 publications
(527 reference statements)
4
28
0
Order By: Relevance
“…The emergence of dominant zonal wavenumbers associated with extreme meridional energy transports also has implications for teleconnections. Investigations based on large deviation theory have shown that persistent weather extremes are associated with very large scale atmospheric features Gálfi et al (2019); Galfi and Lucarini (2021); Gálfi et al (2021). We emphasized here the similarity between our results and the concurrent emergence of heat waves across the Northern Hemisphere associated with a persistent k = 5 − −7 Rossby wave pattern, as found by Kornhuber et al (2020).…”
Section: Discussionsupporting
confidence: 85%
“…The emergence of dominant zonal wavenumbers associated with extreme meridional energy transports also has implications for teleconnections. Investigations based on large deviation theory have shown that persistent weather extremes are associated with very large scale atmospheric features Gálfi et al (2019); Galfi and Lucarini (2021); Gálfi et al (2021). We emphasized here the similarity between our results and the concurrent emergence of heat waves across the Northern Hemisphere associated with a persistent k = 5 − −7 Rossby wave pattern, as found by Kornhuber et al (2020).…”
Section: Discussionsupporting
confidence: 85%
“…Heatwave definition. Let us precisely define heatwaves, as proposed for the present work and following recent studies (Ragone et al, 2018;Gálfi et al, 2019;Gálfi et al, 2021;Bouchet, 2019, 2021;Galfi and Lucarini, 2021). For that, it is first needed to define the fluctuations in temperature and geopotential height, which are called anomalies when the fluctuations are large.…”
Section: Climate Data and Heatwavesmentioning
confidence: 99%
“…As explained in the introduction, this definition of heat-waves follows seminal studies (Schär et al, 2004;Barriopedro et al, 2011;Coumou and Rahmstorf, 2012) of the 2003 and 2010 heatwaves; it is specifically suited for the study of high impact events, and has been adopted in a set of recent studies (Ragone et al, 2018;Gálfi et al, 2019;Gálfi et al, 2021;Bouchet, 2019, 2021;Galfi and Lucarini, 2021). Heatwave prediction dataset.…”
Section: Climate Data and Heatwavesmentioning
confidence: 99%
See 2 more Smart Citations